2012
DOI: 10.1017/s1368980012004405
|View full text |Cite
|
Sign up to set email alerts
|

Impact of counselling on exclusive breast-feeding practices in a poor urban setting in Kenya: a randomized controlled trial

Abstract: Objective: To determine the impact of facility-based semi-intensive and home-based intensive counselling in improving exclusive breast-feeding (EBF) in a low-resource urban setting in Kenya. Design: A cluster randomized controlled trial in which nine villages were assigned on a 1:1:1 ratio, by computer, to two intervention groups and a control group. The home-based intensive counselling group (HBICG) received seven counselling sessions at home by trained peers, one prenatally and six postnatally. The facilityb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
69
2
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(76 citation statements)
references
References 25 publications
(64 reference statements)
3
69
2
2
Order By: Relevance
“…26 Additionally, in a study conducted in Kibera slum Nairobi older mothers were more likely to breastfeed. 20 Conversely, younger mothers were more likely to practice exclusive breastfeeding as reported by Ogada. Another demographic factor found to influence exclusive breastfeeding was marital status.…”
Section: Demographic Characteristicsmentioning
confidence: 89%
See 3 more Smart Citations
“…26 Additionally, in a study conducted in Kibera slum Nairobi older mothers were more likely to breastfeed. 20 Conversely, younger mothers were more likely to practice exclusive breastfeeding as reported by Ogada. Another demographic factor found to influence exclusive breastfeeding was marital status.…”
Section: Demographic Characteristicsmentioning
confidence: 89%
“…19 Additionally, Ochola et al noted that increased workload hinders exclusive breastfeeding. 20 Housewives and mothers of lower socioeconomic status were predictors of exclusive breastfeeding. Working mothers were reported to have lower breastfeeding rates compared to non-working mothers and this could be due to lack of adequate time to exclusively breastfeed their infants.…”
Section: Socioeconomic Factorsmentioning
confidence: 98%
See 2 more Smart Citations
“…A systematic review in high-income settings indicated that successful counseling-based EBF interventions respond in real time to breastfeeding difficulties encountered during feeding, offer peer support, consist a long duration of followup after delivery, and maintain frequent contact with mothers. 24 These suggestions are supported by recent studies in Kenya, 25,26 Ghana, 27 and South Africa, 28 where peer mentorship and frequent counseling sessions over a long duration were required to influence EBF. EBF promotion efforts among HIV-infected women in sub-Saharan Africa feature additional barriers and challenges.…”
mentioning
confidence: 83%